Feasibility study of a novel wearable sweat sensor for anaerobic threshold determination - Luo, Zhixuan; Cao, Menglu; Yan, Lin; Wang, Jun (Scientific reports, 2025)
Lactate anaerobic threshold has been a commonly used metric in the field of training monitoring, however its invasiveness has been overwhelming. Therefore, this study utilized sweat sensors to monitor Na + and K + in sweat to investigate the possibility of using sweat for anaerobic threshold monitoring. Fifty-five subjects were asked to complete an incremental load riding test. The test started at 100 W and each level of load lasted 3 min with one minute of rest in increments of 25 W/3min until exhaustion. Sweat collection was performed on the left chest throughout the ride to test sweat Na + and K + concentrations at each level, and fingertip blood collection was performed to measure blood lactate concentrations. For high and middle level populations, sST and sPT showed higher correlation and agreement with bLT (HL: sST vs. bLT: r = 0.559 p < 0.05,sPT vs. bLT: r = 0.667 p < 0.05;ML: sST vs. bLT: r = 0.802 , p < 0.01, sPT vs. bLT: r = 0.723 p < 0.01), whereas for low level populations the method may not predict anaerobic threshold. The findings validates the possibility of sweat monitoring on anaerobic threshold testing, which suggests that sweat metrics are linked to energy metabolism metrics, which could help to advance sweat monitoring in the field of exercise practice. Further research is needed to advance exploration in this field.